On the origin and meaning of the German word Luft and some meteorological terms concerning atmospheric water, especially fog - Möller, Detlev (DIE ERDE – Journal of the Geographical Society of Berlin, 2014)
The English and French word “air” is derived from the Latin aer, which comes from the Greek άήρ. In contrast, the German word “Luft” is a common Proto-Germanic word; in Old English “ lift” and “ lyft”. The word Luft (also Danish, Swedish and Norwegian) is associated with brightness; the German Licht (light), an air (in an atmospheric sense) without fog or clouds. Air and water were originally “elements” in ancient Greek and were transmutable; they represented two kinds of the “ layer of mist” (atmosphere). Dark or thick air was mist or cloud, hiding the gods (who lived in the upper air or sky; the aether). Different terms are presented that describe fog and clouds in connection with the history of the process of understanding. Finally, the word Luft (air) as a term for gaseous chemical compounds (“ kinds of gases”) is discussed. In addition to the German, all terms are given in Greek, Latin, English and French.